Sławomir Soczyński, (Re)definition of the concept of the media taboo as an axionormative category from a theoretical and functional perspective, Kraków 2021, ss. 331 ISBN 978-83-7720-665-2. - Leśniczak, Rafał (Folia Toruniensia, 2022)
The aim of Sławomir Soczyński’s monograph (Re)definition of the concept of media taboo as an axionormative category from a theoretical and functional perspective is an attempt to understand the phenomenon of media taboo, to show its importance for participants of mediatized communication processes, and thus to show taboo as an element of the system that regulates the space of the mediasphere. The monograph consists of two parts: the first, comprised of two chapters, conceptualizes the concept of taboo in theoretical media studies, and the second part, comprised of four chapters, is a pragmatic study of taboos in the mediasphere. The research contained in the book is situated in the field of social sciences in the discipline of social communication and media science.